Euthanasia, as a legal and ethical issu - RABIEGA, REMIGIUSZ (Prawo Kanoniczne, 2017)
In this article, the author discusses the issue of euthanasia mainly from the point of view of Polish criminal law and in terms of ethical standards. These standards significantly shape the society, affecting also on the appearance of the legislation. Since the legislature has decided to describes the type of euthanasia (murder at the request and under the influence of compassion) in the penal code, it must mean, that such behavior despite (it might seem) a manifestation of mercy - must demonstrate a certain degree of social harm. Moreover, this act forbidden under threat the penalty, confirms the limitations in the disposal of legal goods, which have an universal character. This means that even in the case of agreement (here even required or demanded from the killed person) offender can not be inculpabled. In addition to the legal nature, euthanasia shows primarily relationship with an ethical realm. Both: the Hippocratic Oath and the science of the Catholic Church, considers human life as the most important good. This means that nobody is allowed to decide on taking someone else's life. Legalized euthanasia may therefore constitute a significant threat, so be sure to think about where is the line between sacrum and profanum